2005
DOI: 10.1016/j.nuclcard.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo measurement of vascular inflammation with F-18 fluorodeoxyglucose positron emission tomography

Abstract: These data show that FDG accumulates in macrophage-rich atherosclerotic plaques and demonstrate that vascular macrophage activity can be quantified noninvasively with FDG-PET. As such, measurement of vascular FDG uptake with PET holds promise for the noninvasive characterization of vascular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(185 citation statements)
references
References 44 publications
10
169
1
1
Order By: Relevance
“…[29], uptake has been shown to strongly correlate (r = 0.81, P < 0.0001) with plaque macrophage content, and this has been confirmed by others [30][31][32]. After balloon aortic injury in New Zealand white rabbits, Tawakol et al [33] demonstrated again a very strong correlation (r = 0.93, P < 0.002) between FDG uptake into atherosclerotic regions and plaque macrophage content. FDG uptake was 19 times greater in the region of greatest plaque formation as compared to controls.…”
Section: Vascular Imaging With Fdg-petmentioning
confidence: 68%
“…[29], uptake has been shown to strongly correlate (r = 0.81, P < 0.0001) with plaque macrophage content, and this has been confirmed by others [30][31][32]. After balloon aortic injury in New Zealand white rabbits, Tawakol et al [33] demonstrated again a very strong correlation (r = 0.93, P < 0.002) between FDG uptake into atherosclerotic regions and plaque macrophage content. FDG uptake was 19 times greater in the region of greatest plaque formation as compared to controls.…”
Section: Vascular Imaging With Fdg-petmentioning
confidence: 68%
“…Because the metabolic and apoptotic signals are large, it is likely that even small lesions will be visible [18]. For these reasons, Tc-labeled annexin A5, a SPECT tracer as a marker of ongoing apoptotic cell death, and 18 F-FDG, a PET tracer as a marker of inflammation, are being evaluated for detecting vulnerable atherosclerotic plaques [18][19][20][21][22][23]. It…”
Section: Introductionmentioning
confidence: 99%
“…In murine experiments, a strong correlation between FDG uptake and gene expression of inflammatory molecular markers has been demonstrated (21). Building on these early findings, in rabbits, it has been shown that inflamed aortic lesions accumulate up to 20 times more FDG than non-inflamed arterial lesions, thereby enabling reliable noninvasive detection of inflamed loci within arterial wall with FDG-PET (20). From these studies, it becomes clear that the PET derived FDG signal can be reliably used as a beacon for arterial wall inflammation.…”
Section: Basis For Arterial Fluorine-2-deoxy-d-glucose (Fdg) Uptake Fmentioning
confidence: 94%
“…Several studies have established a strong correlation between arterial FDG uptake and macrophage content in a variety of animal models (18)(19)(20). In murine experiments, a strong correlation between FDG uptake and gene expression of inflammatory molecular markers has been demonstrated (21).…”
Section: Basis For Arterial Fluorine-2-deoxy-d-glucose (Fdg) Uptake Fmentioning
confidence: 98%